Multispectral backscatter-based characterization of seafloor sediments using calibrated multibeam and tilted single-beam echosounders - Fezzani, Ridha; Berger, Laurent; Le Bouffant, Naig; Lurton, Xavier (Frontiers in Remote Sensing, 2025)
This study presents a detailed analysis of Angular Response Curves (ARC) extracted from a multi-spectral seabed backscatter dataset utilizing both calibrated single-beam (SBES) and multibeam echosounders (MBES). Five calibrated SBES transducers were tilted from −9° to 70° to measure ARC at different discrete frequencies ranges from 35 kHz to 440 kHz (three to four frequencies per transducer). Additionally, three frequencies −200 kHz, 300 kHz and 400 kHz - were used with the MBES. Experimental data were collected in the Bay of Concarneau, located on the French Northwest coast, across seven different ground-truthed sediment types. The study aims to investigate the effects of frequency and pulse length on ARC shape and intensity. Furthermore, a novel method for estimating seabed angular backscatter from standard SBES volume backscatter strength (Sv) is used. A key aspect of this research is the intercalibration of the multibeam and singlebeam systems to ensure consistency and reliability in MBES backscatter measurements. These findings contribute to a better understanding of acoustic wave interactions with sediment properties across different wavelengths and pulse durations, ultimately improving seabed characterization accuracy.